2004
DOI: 10.1111/j.0022-202x.2004.22609.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Black and White Skin to Solar-Simulating Radiation: Differences in DNA Photodamage, Infiltrating Neutrophils, Proteolytic Enzymes Induced, Keratinocyte Activation, and IL-10 Expression

Abstract: Black skin is more resistant to the deleterious effects of ultraviolet radiation than white skin. A higher melanin content and a different melanosomal dispersion pattern in the epidermis are thought to be responsible for this. Our purpose was to compare skin responses in black and white skin following exposure to solar-simulating radiation (SSR) to further investigate the photoprotective properties of black skin. Six volunteers of skin phototype I-III (white) were exposed to (doses measured directly with a Wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 29 publications
9
69
0
4
Order By: Relevance
“…they burn more and tan less than a person with higher pigmentation. In this respect Rijken et al [28] recently compared the responses of black and white skin to solar-simulating radiation and except for some DNA damage in the suprabasal epidermis the subjects with skin of colour did not show any increase in neutrophils, active proteolytic enzymes and diffuse keratinocyte activation unlike the Caucasians. Thus, it would appear that Asian skin has other mechanisms than the presence of melanin to protect against UV irradiation.…”
Section: Differences In Skin Colorationmentioning
confidence: 99%
“…they burn more and tan less than a person with higher pigmentation. In this respect Rijken et al [28] recently compared the responses of black and white skin to solar-simulating radiation and except for some DNA damage in the suprabasal epidermis the subjects with skin of colour did not show any increase in neutrophils, active proteolytic enzymes and diffuse keratinocyte activation unlike the Caucasians. Thus, it would appear that Asian skin has other mechanisms than the presence of melanin to protect against UV irradiation.…”
Section: Differences In Skin Colorationmentioning
confidence: 99%
“…The patterns of skin aging are characterized by ethnic specificity among different peoples (Chung et al, 2001;Rijken et al, 2004); for example, pigmentation and wrinkling patterns in yellow skin share little common features with those in white skin (Roh et al, 2001). Nouveau-Richard et al(2005) reported main skin aging features progress differently in Chinese and French women, and Zhao et al(1998) investigated 470 healthy people in Northeast China to explore skin damage resulting from solar ultraviolet (UV) radiation.…”
Section: Introductionmentioning
confidence: 99%
“…A més, la mala resposta de la pell a l'exposició al sol, amb l'aparició de cremades i la impossibilitat de bronzejat, és també un indicador d'una major susceptibilitat al càncer de pell, sobretot al melanoma. En individus amb trets de pigmentació més foscos i amb millor tolerància al sol, la incidència de neoplàsies cutànies és menor a causa del nivell més elevat de melanina epidèrmica, la qual exerceix com a factor fotoprotector, capaç d'absorbir la radiació UV (Liu i altres, 2013;Rijken i altres, 2004;Scherer i Kumar, 2010).…”
Section: El Càncer De Pellunclassified